2014
DOI: 10.1002/2013jd021215
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of tropospheric ozone over an urban site in India: A study based on MOZAIC and CCM vertical profiles over Hyderabad

Abstract: This study is based on the analysis of Measurement of Ozone and Water Vapor by AirbusIn-Service Aircraft (MOZAIC) data measured over Hyderabad, India during the years 2006-2008. Tropospheric profiles of O 3 show clear seasonality with high and low values during the premonsoon and monsoon seasons, respectively. Analysis of back trajectory and fire count data indicates major roles for long-range transport and biomass burning in the seasonal variation of O 3 . Typically, lower levels of O 3 in the monsoon season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…The relation of tropical biomass burning and tropospheric ozone had been studied during intense fires over Indonesia in 1996-1998 by Thompson et al (2001). The Indonesian fires of 2006 were studied by Ott et al (2010), Zhang et al (2011), Srivastava and Sheel (2013) and Sahu et al (2014). Results showed that biomass burning emissions are responsible for an increase in O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The relation of tropical biomass burning and tropospheric ozone had been studied during intense fires over Indonesia in 1996-1998 by Thompson et al (2001). The Indonesian fires of 2006 were studied by Ott et al (2010), Zhang et al (2011), Srivastava and Sheel (2013) and Sahu et al (2014). Results showed that biomass burning emissions are responsible for an increase in O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the simulation used in this study is the same as that in Sahu et al . [], it is only briefly mentioned here. In the simulation, the horizontal wind field was nudged toward the Japan Meteorological Agency Climate Data Assimilation System (JCDAS) analysis [ Onogi et al ., ].…”
Section: Observation and Model Simulationsmentioning
confidence: 99%
“…The Global Fire Emissions Database, version 3 (GFEDv3) inventory [ van der Werf et al ., ] estimated the global annual totals to be in the range of 250 to 600 Tg/yr. Typically, the higher annual emissions from biomass burning sources coincide with a very intense El Niño–Southern Oscillation (ENSO) episode, also seen at regional scales [ Duncan et al ., ; Sahu et al ., ]. The 1997–2009 average global fire emissions of CO had a contribution of 44% from Africa and 22% from equatorial and Southeast Asia [ van der Werf et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al, 2008;Elguindi et al, 2010;Kalabokas et al, 2007Kalabokas et al, , 2013Petetin et al, 2016aPetetin et al, , 2016bSahu et al, 2014;Sauvage et al, 2005;Sheel et al, 2016;Tressol et al, 2008;Yamasoe et al, 2015). However, a part of the scientific community seems reluctant to use the IAGOS data for studying the lowermost PBL due to concerns about the representativeness of the IAGOS measurements close to the surface.…”
Section: Introductionmentioning
confidence: 99%